Eating Habits of University Students Living at, or Away From Home in Greece - Papadaki, A.; Hondros, G.; Scott, Jane; Kapsokefalou, M. (Elsevier BV, 2007)
The aim of this study was to assess the effect of living away from, or in, the family home on the dietary habits of a group of Greek undergraduate University students. Eighty-four undergraduates at Athens Agricultural University, aged 20–24, completed a single, selfadministered food habits questionnaire that asked about their current food practices and their food practices before they started University. Students living at home did not show major changes in their eating habits since starting University. Although students living away from the family home had made some positive changes, they decreased their weekly consumption of fresh fruit, cooked and raw vegetables, oily fish, seafood, pulses and olive oil, and increased their sugar, wine, alcohol and fast food intake. Between group comparisons of dietary changes showed that since starting University, students living away from home had developed more unfavourable eating habits than students living at the family home. These findings suggest that moving away from the family home and assuming responsibility for food preparation and purchasing for the first time affect dietary habits in this sample of Greek University students. Nutrition interventions in this young population should be encouraged to promote healthier diets and lifestyles, as well as adherence to the traditional Mediterranean diet.